2016
DOI: 10.1007/s12011-016-0829-6
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of a Lotus Leaf Selenium (Se)-Polysaccharide in Rats with Gestational Diabetes Mellitus

Abstract: A selenium (Se)-containing polysaccharide, lotus leaf selenium (Se)-polysaccharide (LLP), was isolated from a lotus leaf. The effects of LLP on antioxidant enzyme activities and insulin resistance in pregnant rats with gestational diabetes mellitus (GDM) were investigated. LLP administered orally at two doses (50 and 100 mg/kg) could significantly reverse the weight loss of pregnant rats before the delivery, fetal rats, and placentas in GDM rats (P < 0.05). Furthermore, LLP treatment induced a decrease of fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…The similar anti-diabetic activity of lotus leaf was also reported by other researchers. Zeng et al (2016) found that the treatment of rats with gestational diabetes mellitus with 50 and 100 mg/kg lotus leaf selenium-polysaccharide, a water extract of lotus leaf, for 2 weeks induced a significant decrease in FBG and insulin levels. Huang et al (2011) reported that lotus leaf methanolic extract (100 mg/kg) also significantly decreased blood glucose levels of normal mice and HFD-induced diabetic mice.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The similar anti-diabetic activity of lotus leaf was also reported by other researchers. Zeng et al (2016) found that the treatment of rats with gestational diabetes mellitus with 50 and 100 mg/kg lotus leaf selenium-polysaccharide, a water extract of lotus leaf, for 2 weeks induced a significant decrease in FBG and insulin levels. Huang et al (2011) reported that lotus leaf methanolic extract (100 mg/kg) also significantly decreased blood glucose levels of normal mice and HFD-induced diabetic mice.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, studies performed by Du et al (2010) and Guo et al (2013) found that lotus leaf hot water extract or its major active aporphine alkaloid nuciferine significantly reduced the serum TG, TC and LDL-c levels in HFD fed SD rats or hamsters. 1% lotus leaf ethanol extract or 50 or 100 mg/kg lotus leaf selenium-polysaccharide also significantly elevated HDL-c levels in db/db mice and gestational diabetes mellitus rats in addition to its role in reducing TG, TC, and LDL-c levels (Kim et al, 2013; Zeng et al, 2016). The different results between ours and literatures may be explained by the different concentrations and action time of lotus leaf or different origins and extraction methods of lotus leaf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, some kinds of β-glucans have been identified to regulate energy homeostasis. Lotus leaf selenium-polysaccharide and oat β-glucan can alleviate insulin resistance and show anti-obesity functions in diabetes mice models [ 27 , 28 ]. However, whole-grain barley β-glucan fermentation did not improve glucose tolerance in rats fed with HFD [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lotus leaves from Nymphaeaceae has been recognized as a precious Chinese medicine for both pharmaceutical and food usage and is widely farmed in China for its high economic value [1,2]. The major active ingredients of lotus leaf are alkaloids such as nuciferine, O-demethyl nuciferine, and N-demethyl nuciferine, whose pharmacological activities contribute significantly to hypolipidemic, weight-losing, antibacterial, antiviral, seductive, and anticonvulsive effects, despite the rather low content in lotus leaves [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%